Recuperación biotecnológica de quitina de residuos de crustáceos - Sirvas-Cornejo, Susana (2020)
Reviews on biotechnological chitin recovery from crustacean waste and other sources acknowledge. Most of the reviews conclude that although important results on chitin recovery have been achieved, there is still a need for better approaches to improve operational conditions of deproteinization and demineralization processes, such as time, carbon source, pH (initial and during fermentation), volume of inoculum, temperature, among others, in order to apply at industrial level, a bioprocess commercially and environmentally cost/effective viable. The present review aims to gather the most updated available information about research on biotechnological methods to recover chitin from crustacean waste, studied during the past 10 years, focussing on conditions applied to deproteinization (DP) and demineralization (DM), particularly on bioprocessing times and microbial species.